A hybrid scheme of load shedding using globalized frequency and localized voltage (GFLV) controller. (December 2019) - Aman, M.M.; Arshad, Muhammad; Zuberi, H.K.; Laghari, J.A.
Highlights: A novel hybrid load shedding technique is proposed in this paper. Proposed technique is based on localize voltage and globalized frequency. The proposed strategy is implemented through simulation on PSCAD/EMTDC. Improved voltage and frequency stability of power system. Load priority strategy is used for UFLS. Abstract: Load shedding is a control action to maintain the stability of power system by disconnecting the load in case of electricity shortfall. For the safe operation of electrical power system, it is necessary that frequency and voltage should be within the specific range. In this paper, a novel load shedding technique is proposed based on globalized frequency and localized voltage (GBLV). The proposed strategy is implemented through simulation on PSCAD/EMTDC. Simulations results reveal that the proposed schemes are successfully catering the decline in frequency and voltage by performing adaptive load shedding to sustain the stability of power system.